The conditional stability and an iterative regularization method for a fractional inverse elliptic problem of Tricomi-Gellerstedt-Keldysh type - Djemoui, Sebti; Meziani, Mohamed S. E.; Boussetila, Nadjib (Mathematical Modelling and Analysis, 2024)
The present paper is devoted to identifying an inaccessible boundary condition for a fractional elliptic problem of Tricomi-Gellerstedt-Keldysh-type. Using the expansion Fourier method, the considered problem can be reformulated as an operator equation of the first kind. To construct a stabilized approximate solution we employ a variant of the iterative method. We also present error estimates between the exact solution and the regularized solution by the a priori and the a posteriori parameter choice rules. Finally, some numerical verifications on the efficiency and accuracy of the proposed algorithm is presented.